Pengaruh Permainan Puzzle Terhadap Kemampuan Pemecahan Masalah Anak Usia 4-5 Tahun - Dwi Permata, Rista (Universitas Nusantara PGRI Kediri, 2020)
Problem solving is one aspect contained in the cognitive. Considering that early childhood is still in the learning phase to be familiar with the conditions of the surrounding environment, including all existing problems, it is strongly recommended that the learning activities given refer to problem solving exercises. Children learn through play, by using puzzle media to practice their thinking skills in problem solving. The purpose of this study is to determine the effect of the use of puzzle game media on the ability to solve child problems. The design in this study uses one group pretest-posttest design. The class determination of the experiment was carried out randomly. This research was applied in PKK Harapan Rahayu Kindergarten, Soko District, Tuban Regency with a sample of 34 children, which were then divided into 2 groups (experimental and control). Data collection techniques in this research use observation and documentation. This research utilizes quantitative descriptive data analysis techniques, which means describing the data that has been collected through the activities of children and teachers during the learning process. The data analysis was carried out using the Independent Samples Test which showed a sig (2-tailed) result of 0,000 <0.05. So it can be concluded that the puzzle game media influence in improving problem solving abilities in early childhood.